Inisiasi Pemberdayaan PCM Mlati dalam Peningkatan Kesehatan Jiwa Umat dalam Masa Pandemik Covid-19 - Yanuar Fahrizal; Nina Dwi Lestari; Ida Rochmawati (Universitas Lancang Kuning, 2021)
The spread of covid-19 throughout the world has led to an increase in global health status. Covid-19 pandemic in addition to problems in the human body can also cause stress and increase the risk of various psychiatric problems. Muhammadiyah's Business Charity at PCM Mlati currently still focuses on education and religion and has just spearheaded a charity working in the health field in the form of the klinik pratama. At the time of this pandemic, PCM Mlati members and the surrounding community had not yet received optimal mental health promotion and prevention services from health workers. Mental health is as important as physical health because if someone has psychiatric problems can cause other problems so the problem becomes very complex. The solutions offered include: early detection, health education with materials such as stress management through effective communication during a pandemic and optimizing comfort zones and mental health counseling. Early detection results show that the majority of normal / healthy mental health status is 61.11%